The use of Carbon-Peek volar plate after distal radius osteotomy for Kienbock’s Disease in a volleyball athlete: a case report - Guzzini, Matteo; Princi, Giorgio; Proietti, Lorenzo; Ferretti, Andrea (Acta Biomedica Atenei Parmensis, 2019)
Kienbock’s Disease, or lunatomalacia, has uncertain etiopathogenesis, it is more common in male from 20 to 45-year-old. The Lichtman’s classification is the most used by authors and it divides Kienbock’s Disease in 4 stages according to radiographic parameters. In early stages could be performed a conservative treatment, but failure rate is high; various surgical techniques are available in case of failure or higher stages. We report a case of a 26-year-old female volleyball player affected by stage I Kienbock’s Disease who underwent distal radius osteotomy core decompression synthesized with Carbon-Peek plate fixation. Follow-up was performed with clinical evaluation (ROM analysis, VAS score, Quick Dash Score), wrist radiographs and wrist MRI.